Concurrent tuberculosis and COVID-19: reports of three cases (BIRDEM Medical Journal, 2020)
Coronavirus disease 2019 (COVID-19), the latest global pandemic is on the hunt and the incidence is sharply rising day by day. On the other hand, tuberculosis (TB) is the leading causes of death from infectious origin. Historically, coronaviral illness were reported with co-infection with TB; Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is not an exception. As both diseases have overlapping clinical features, sometimes it maybe very difficult to diagnose and long standing features of TB can easily be mistaken for post-acute COVID-19. This report emphasizes the importance of suspecting TB-COVID co-infection and its grave consequences.Birdem Med J 2020; 10, COVID Supplement: 111-114